Determinants of Income Inequality in Egypt Using the Autoregressive Distributed Lags Model “Comparison Study between Rural and Urban Areas” - Agbo , Hanan (The Arab Journal of Administration, 2020)
The issue of poverty alleviation for the poor and low income is one of the most important issues in the decision maker’s agenda, achieving this goal requires a mix of country-specific growth and distribution policies. Therefore, the study aims to analyze the changes in the pattern of consumption expenditure in Egyptian rural and urban areas, and estimate the indicators of poverty and income inequality. In addition to analyzing the determinants of income inequality using the Autoregressive Distributed Lags Model (ARDL). In the study we analyzed changes in the pattern of consumption expenditure in Egyptian rural and urban areas, we found that the highest expenditure of households in both rural and urban areas is on the food and drink group, followed by expenditure on housing and its necessities, expenditure on services and health care and the lowest expenditure on cultural activities and entertainment. The consumption of food commodities in both rural and urban areas is also different. Consumption of milk, cheese, eggs, fish and fruit is higher in urban areas compared to rural areas, while consumption of vegetables, grains and oils in rural areas is higher than that of urban areas. Consumption of meat in both rural and urban areas is highest in food consumption. The study also examined the determinants of inequality in income distribution using the methodology of the boundary between the Gini coefficient and the main macroeconomic variables using the Autoregressive Distributed Lags Model (ARDL) methodology. The results of the study were as follows: There is an inverse relationship between trade openness and Gini coefficient in both the short and long terms. There is a significant positive relationship in the short term between the rate of inflation and income inequality. There is a significant indirect relationship in the short term between government expenditure and income inequality. This means the lack of fiscal policy to decrease income inequality in short-run. In the long run, the relationship is morally reversible. This means that long-term fiscal policy contributes to improving equity among households and targeting poorer families, thus reducing income inequality. Increasing capital formation leads to a reduction in income inequality in the short term. In the long term, the relationship is positive, as the increase in capital formation negatively affects employment and consequently leads to increased inequality in income distribution. There is a significant inverse relationship in the short term between GDP and Gini coefficient. However, in the long run, the relationship is positive. Thus, the fruits of economic growth are distributed in the direction of a specific category. This means the non-applicability of Kuznets’ theory (1955), which shows that the income inequality increases in the early stages of growth, but tends to decline in the later stages and the Kuznets curve takes the reverse U shape. There is a significant long-term correlation between the rate of population growth and income inequality. There is a positive relationship in the long term between unemployment rate and income inequality, but this relationship is not significant.